Increasingly lonely Peranakan - Abd Razak, Dzulkifli (2008)
"IT is lonely to be a Malaysian." This was what Emeritus Professor Khoo Khay Kim said when we met last week at the inaugural National Conference on Penang Peranakan Chinese and Chinese Muslims. Coincidentally, on the same day, some Malaysians were filing their nomination papers for the impending elections. Going by the crowds and shouts they drew, it was far from lonely. Instead, the mood was rather festive, with bunting and flags of various colours and sizes. What the professor meant, I thought, goes beyond the superficial tangibles that meet the eye. For example, how comfortable are the citizens of this country when it comes to going beyond their comfort zone of ethnicity, religious beliefs and cultural practices?